A vapor phase hydrothermal modification method converting a honeycomb structured hybrid film into photoactive TiO2 film - Zhao, Huijun (Langmuir : the ACS journal of surfaces and colloids, 2009)
Transforming an organic/inorganic hybrid material into a pure inorganic material without losing its original structure is of interest for a range of applications. In this work, a simple and effective vapor phase hydrothermal method was developed to transform a 3D honeycomb structured PS/TTIP hybrid film into a photoactive TiO2 film without dismantling the originally templated 3D structure. The method utilizes the vapor phase hydrothermal process to create titania network/clusters with sufficient mechanical strength via the formation of Ti-oxo bridges. The organic components of the sample can be removed by means of pyrolysis while perfectly maintaining the original 3D honeycomb structure. The resultant film can be directly used for photocatalysis applications and could be further modified for other applications. In principle, this method can be used to preserve 3D structures of other organic/inorganic hybrid films during their conversion to pure inorganic films via a pyrolysis process, if mechanically strong networks can be formed as a result of hydrolysis reactions. The ability to preserve the preferred 3D structure during the subsequent conversion processes enables realization of the full benefit of unique architectures created by a templating method